Recent developments in the diagnosis and management of N1 penile cancer. Issue 1 (7th January 2023) - O'Brien, Jonathan S.; McVey, Aoife; Kelly, Brian D.; Chee, Justin; Lawrentschuk, Nathan
Abstract : Purpose of review: This article presents a critical review of the current literature to provide a brief update on the contemporary advances in diagnosing and managing N1 penile cancer. Recent findings: Penile squamous cell carcinoma (pSCC) has evolved from being an orphan field for cancer innovation. Advances in the understanding tumour biology have enabled sophisticated diagnostics and predictive modelling to better characterize inguinal disease. Minimally invasive inguinal lymph node dissection is emerging as a technique that reduces morbidity while maintaining oncological safety. Furthermore, robust clinical trials are underway, which will provide level one evidence to guide treatment decisions. Exciting advances in the field of immune-oncology offer promise as adjuvant therapies. International collaboration and centralisation of care will be essential to driving translational research and equitable evidence-based care. Summary: Improving outcomes for men with pSCC remains a global challenge. Radical inguinal lymph node dissection remains the gold standard for diagnosing and curing N1 disease. Although many promising developments are on the horizon, high-level evidence is required to guide therapy.